Maintenance and performance of ferry terminal / Nurzawani Ahmad Shukri - Ahmad Shukri, Nurzawani (Faculty of Architecture, Planning and Surveying, 2010)
This research is concerned with the issues of users’ satisfaction in maintenance management and performance of maintenance works in ferry terminal. Ferry terminal are chosen as subject discussed due to the reason that ferry terminal is public building and involved many people, it important to ensure the building can make comfortable and safety to the occupant. The primary aim of this study is to identify the satisfaction levels and users and occupants in ferry terminal. This dissertation includes the outlines of the introduction to the subject and each subtopic, and also explained elaborately about building maintenance, and ferry terminal building. Research methodology which had been applied in the two cases study are through literature review, questionnaire survey to the ferry terminal occupants, interview session with maintenance staff in marine department and observation of overview of the ferry terminal. Then,, data analysis and findings between cases study is based on literature review, research method and additional outsource references.. Finally, conclusion is made according to research findings and development of recommendation for future improvement of maintenance quality in ferry terminal.